Some characteristics and allopurinol release of carrageenan/ allopurinol films using polyethylene oxide as a dispersion aid agent - Phuong, Nguyen Thi; Chinh, Nguyen Thuy; Manh, Vu Quoc; Hoang, Thai; Trung, Vu Quoc (Vietnam Journal of Science and Technology, 2020)
This paper presents the effect of carrageenan (CG) on some characteristics and drug release of allopurinol in the presence of polyethylene oxide (PEO) as a dispersion aid agent. The samples were prepared in film shape by solution method, in which, the content of PEO was changed from 1 wt.% to 5 wt.% and the content of allopurinol was fixed at 10 wt.% in comparison with carrageenan weight. FTIR , FESEM, UV-Vis methods were used to evaluate characterizations and morphology of CG/PEO/allopurinol films.